Antiseptik Oral yang Efektif dalam Pencegahan Ventilator-Associated Pneumonia - Rusdi, Ainur (Universitas Muhammadiyah Surabaya, 2021)
Objective: Pneumonia is the most common infection in mechanically ventilated patients in the intensive care unit (ICU). Oral care is one way to prevent ventilator-associated pneumonia (VAP). Oral antiseptics that are widely mentioned in the literature are chlorhexidine, listerin, povidone iodine, sodium bicarbonate, normal saline, and sterile water. Methods: The sources of the articles used were obtained from searches through databases including Google Scholar, Science Direct, Springerlink, PubMed, and Pro Quest. This search was limited from 2002 to 2014. Once found, then an article review was carried out up to the stage of making a literature review. Results: Oral antiseptic chlorhexidine 0.2% and chlorhexidine 0.12% proved to be more effective than listerin, 1% povidone iodine, sodium bicarbonate, normal saline, and sterile water. Conclusion: 0.2% chlorhexidine and 0.12% chlorhexidine are the most effective oral antiseptics for oral care of critically ill patients who use mechanical ventilation to prevent ventilator-associated pneumonia (VAP)